Graphene-based ultra-wideband absorber for terahertz applications using hexagonal split ring resonators. (1st June 2022) - Upender, Patri; Kumar, Amarjit
Abstract: In this paper, a hexagonal split ring ultra-wideband absorber is proposed at THz frequency. The proposed structure consists of four graphene based hexagonal split rings, a dielectric substrate and graphene layer at the bottom. The proposed absorber achieves an ultra-wideband absorption characteristics from 0.95 THz to 2.96 THz with percentage bandwidth of 102.8% and bandwidth of 2.1THz with absorptivity beyond 90%. Also, 100% absorption is achieved from 2.07 to 2.33 THz making this unique feature for THz applications. Ultra-wideband response is mainly resulted because of overlapping of strong Electromagnetic (EM) resonance of the four split rings. The modes generated within the graphene split rings are merged for achieving ultra wide band response. Furthermore, the proposed absorber is polarization insensitive because of symmetry geometry and also exhibits absorption greater than 90% for incidence angle up to 75° for both TE and TM waves. In addition, tunability is achieved by varying the graphene chemical potential. These features make the proposed metal free absorber useful for terahertz applications and future nanoscale systems. The proposed absorber shows narrow absorption characteristics for higher graphene chemical potential values which can also be utilized for sensor applications.